A Review of Perforator Flaps for Burn Scar Contractures of Joints. Issue 1 (February 2019) - Lewinson, Ryan T.; Capozzi, Lauren C.; Johnson, Kody; Harrop, Alan Robertson; Fraulin, Frankie O. G.; Nickerson, Duncan
Objective: Perforator flaps are one possible surgical treatment for burn scar contractures; however, a review of evidence on this topic is lacking. Methods: MEDLINE was searched for articles related to perforator flaps for burn contractures. Following title and abstract screen, full texts were searched to identify articles describing perforator flaps for burn scar joint contractures. Data were extracted and summarized descriptively. Only articles that contained ≥10 patients with burn scar contracture were considered. Results: Two hundred forty-eight articles were identified, of which 17 met criteria for review. Of these, 16 were low-quality case series, while 1 was an open randomized controlled trial. In total, perforator flaps were performed on 339 patients (age range: 3-75 years), with the most common contracture locations being cervical (n = 218) and knee (n = 41). Nine of the 17 articles described a rehabilitation strategy. In general, functional outcomes were excellent, with the majority of patients experiencing return of normal joint range of motion and no recontracture. Compared to full-thickness skin grafts, perforator flaps showed greater improvements in joint range of motion. Cosmetically, perforator flaps were shown to have good color match with surrounding tissue, good contour around anatomical landmarks, and improved overall patient appearance. The most common complications were marginal flap necrosis (n = 26 patients) and venous congestion (n = 17 patients). Conclusions: Preliminary evidence from low-quality case series and 1 high-quality trial suggests perforator flaps may be successful for resurfacing released burn scar contractures; however, there is a need for additional trials comparing perforator flaps to other approaches.